2018
DOI: 10.1186/s12974-018-1114-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxysterol levels and metabolism in the course of neuroinflammation: insights from in vitro and in vivo models

Abstract: BackgroundOxysterols are cholesterol derivatives that have been suggested to play a role in inflammatory diseases such as obesity, atherosclerosis, or neuroinflammatory diseases. However, the effect of neuroinflammation on oxysterol levels has only been partially studied so far.MethodsWe used an HPLC-MS method to quantify over ten oxysterols both in in vitro and in vivo models of neuroinflammation. In the same models, we used RT-qPCR to analyze the expression of the enzymes responsible for oxysterol metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 74 publications
8
45
0
Order By: Relevance
“…This is in line with another study, in which microglia up‐regulated their expression of CH25H during remyelination after toxin‐induced demyelination in the cuprizone mouse model . A recent study supported these findings, by showing that LPS treatment of a microglia cell line led to increased CH25H expression . However, the study also found that the production of the EBI2 ligands 7α,25‐OHC and 7α,27‐OHC was decreased, rather than increased, in response to LPS treatment, presumably due to an increased expression of HSD3B7 and a decreased expression of CYP27A1.…”
Section: Ebi2 In Local Immunity and Autoimmune Diseasessupporting
confidence: 88%
See 4 more Smart Citations
“…This is in line with another study, in which microglia up‐regulated their expression of CH25H during remyelination after toxin‐induced demyelination in the cuprizone mouse model . A recent study supported these findings, by showing that LPS treatment of a microglia cell line led to increased CH25H expression . However, the study also found that the production of the EBI2 ligands 7α,25‐OHC and 7α,27‐OHC was decreased, rather than increased, in response to LPS treatment, presumably due to an increased expression of HSD3B7 and a decreased expression of CYP27A1.…”
Section: Ebi2 In Local Immunity and Autoimmune Diseasessupporting
confidence: 88%
“…However, EBI2 signaling induced by 7α,25‐OHC in astrocytes was shown to decrease their production of pro‐inflammatory cytokines, including IL‐6 and TNF‐α, in response to LPS or IL‐17/TNF‐α treatment . Interestingly, a similar effect was seen using the microglia and astrocyte co‐culture described above, where treatment of LPS‐activated cells with 7α,25‐OHC, and other EBI2 ligands, significantly decreased the production of the pro‐inflammatory cytokine IL‐1β . A similar effect was demonstrated in vivo.…”
Section: Ebi2 In Local Immunity and Autoimmune Diseasesmentioning
confidence: 52%
See 3 more Smart Citations